Fibrinolytic Treatment after Transient Ischaemic Attack Caused by Prosthetic Mitral Valve Thrombosis - Cornel Koban; Michael Neuß; Grit Tambor; Frank Hölschermann; Christian Butter (Case Reports in Cardiology)
Prosthetic valve thrombosis is one of the most severe complications after surgical valve replacement. There are many possible presentations: from asymptomatic to life-threatening complications. We report on a 61-year-old female patient with prosthetic replacement of the aortic and mitral valve in the in-house department of cardiac surgery 3 months ago. The patient was suffering from aphasia during 5 minutes in domesticity. After her presentation in the emergency room, the echocardiographic examination revealed a thrombotic formation of the prosthetic mitral valve. At presentation, the anticoagulation was outside the effective range (INR: 1.7). A successful thrombolytic therapy with the plasminogen activator urokinase was begun with complete resolution of the thrombus.